ANALISIS FREKUENSI KUNJUNGAN PERPUSTAKAAN DALAM MENDORONG PRESTASI AKADEMIK MAHASISWA - Ari Kurniawan; Anton Hermawan; Albertoes Pramoekti Narendra (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2026)
Libraries play a vital role in providing a research ecosystem that supports students in actively seeking information to develop their knowledge. The purpose of this study was to determine the relationship between the frequency of library visits and the academic achievement of Satya Wacana Christian University college students. This research was a correlational study using a quantitative approach. The sample size was 100 college students, selected using a random sampling technique non-probability sampling with the approach purposive sampling. Data collection in this study used a questionnaire. Research data analysis used the assistance of the software IBM SPSS Statistics 25. The results of processing the research data obtained a p value = 0.000 and a correlation coefficient value (rxy) of 0.673**. Based on statistical analysis which means there is a strong and significant relationship between the frequency of library visits and the academic achievement of Universitas Kristen Satya Wacana college students.